2010
DOI: 10.1002/pro.469
|View full text |Cite
|
Sign up to set email alerts
|

Helicity of short E‐R/K peptides

Abstract: Understanding the secondary structure of peptides is important in protein folding, enzyme function, and peptide-based drug design. Previous studies of synthetic Ala-based peptides (>12 a.a.) have demonstrated the role for charged side chain interactions involving Glu/Lys or Glu/Arg spaced three (i, i 1 3) or four (i, i 1 4) residues apart. The secondary structure of short peptides (<9 a.a.), however, has not been investigated. In this study, the effect of repetitive Glu/Lys or Glu/Arg side chain interactions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 29 publications
2
39
0
Order By: Relevance
“…For temperature melts elipticity at 222 nm was monitored over a temperature range of 10°C to 70°C with a temperature slope of 1°C/min and protein concentrations were in the 25–35 μM range. Raw data sets were corrected for buffer contributions and converted to percent helicity as previously described (Sommese et al, 2010; Chen et al, 1974). …”
Section: Methodsmentioning
confidence: 99%
“…For temperature melts elipticity at 222 nm was monitored over a temperature range of 10°C to 70°C with a temperature slope of 1°C/min and protein concentrations were in the 25–35 μM range. Raw data sets were corrected for buffer contributions and converted to percent helicity as previously described (Sommese et al, 2010; Chen et al, 1974). …”
Section: Methodsmentioning
confidence: 99%
“…However, the equivalent study for E–R pairs is lacking. Although it was recently reported that E–R pairs may be more stabilizing than E–K in very short (<12 residue) peptides20, it is unclear which pairings are utilized, or why E–R pairs are more stabilizing.…”
mentioning
confidence: 99%
“…4A bottom), which is ideally situated to form a salt-bridge with native E247 ( i , i +4) 4547 . We chose an R in preference to lysine (K) because properly spaced E-R residues form a helix inside the tunnel 48 and, in solution, have higher helix content than their E-K counterparts 4 . The 243R mutation yields a nascent chain that is compact (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The first step appears to be acquisition of local secondary structures, e.g., helices and turns, followed by folding to a more global native structure 2, 3 . Helix formation depends on the protein’s primary sequence, its solvent environment, and the combination of physicochemical properties that underlie intrahelical side-chain interactions, helical dipole (charge-dipole) interactions, and the effects of other residues flanking the helix 4, 5 . Despite the importance and ubiquity of helical structures in mature proteins, the question of when/where/how these critical structures arise during early biogenesis is still largely unanswered.…”
Section: Introductionmentioning
confidence: 99%